Uji Bioassay pada Hasil Pelaksanaan Indoor Residual Spraying (IRS) dalam Pengendalian Penyakit Malaria - Mawaddah Mawaddah; Marsum Marsum; Dwi Bayu Karti Utami (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
This research was conducted by quasi experimental method, with separate sample pretest post-test control group approach, and counting of the percentage of dead Anopheles spp after contacted for 1 hour with Icon 100 CS insecticide, both for the treatment and the control group. Data analysis was conducted descriptively and statistically by the Anova and LSD test using the software of SPSS version 17. The result of this research shows that in the Village of Bogangin along the time period of the year of 2011-2014 occurred the decrease of the number of positive malaria cases of 97,4%; IRS application in the year of 2014 got success to spray 273 houses (100%) at the target area; the average of the number of dead Anopheles spp mosquitoes after contacted for 1 hour with Icon 100 CS chronolgically at the kind of wall of masonry, wood, and bamboo were 37,66%, 86,63%, and 79,96%. The kind of the sprayed partition effects significantly the percentage of the number of dead Anopheles spp mosquitoes, with number of Sig = 0,007 at level of significant of 95%. To be suggested to review the use of insecticide of Icon 100 CS in the application of IRS.